Towards a Theory of Interim Reporting for A Seasonal Business: A Behavioral Approach. - Bollom, William John (The Accounting Review, 1973)
The article analyzes whether interim data for a seasonal business provide useful information to investors or not. To the foregoing schools of thought related to interim reporting theories, could also be added a nondisclosure approach where the user is not provided with interim information. There is general agreement that the primary objective of the interim report should be to present information with the expressed purpose of enabling the user to predict the annual results of the firm. To establish which interim theory was most useful, a business game was developed in which participants made sequential decisions with respect to investment in firm using different interim reporting methods. Participants worked at their own pace. The two separate economic conditions for each interim reporting method covered a wide spectrum of real reporting conditions. Another possible set of conditions would have included another rising historical earnings trend set followed by a continuation of the rise, and another falling historical earnings trend set followed by a continuation of the fall.